Edukasi Kewirausahaan Bagi Remaja Melalui Media Sosial di Kecamatan Beji Kota Depok - Febriantina, Susan; Aminah, Hania; Herlitah, Herlitah (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
Social media is an effective tool for millennials to learn many things nowadays. However, not all millennials understand how to use social media as a something useful, including entrepreneurial spirit. Therefore, this programme held to 1) emerge teenagers ‘entrepreneurial spirit through social media; 2) socialize social media ethics with its functions for learning. The method used was cooperative learning which matched for teenagers such as explanation, games, question and answer, sharing experience, case study, and discussion. Based on activities evaluation, both knowledge and spirit of the participants (teenagers) about entrepreneurship and social media ethics increased. Furthermore, there will be follow up programs by visiting some entrepreneurship facilities such as Management Business Development Centre (PPMB), Carrier Development Centre (CDC), and Capital Market Laboratory of Economics Faculty Universitas Negeri Jakarta. By this program, we expect that the participants are motivated to develop their entrepreneurship spirit. Keywords: Entrepreneurship, Teenager, Social Media